2017
DOI: 10.20961/ijsascs.v1i2.5136
|View full text |Cite
|
Sign up to set email alerts
|

Influence integrated science model and implamantation learning with the unity of science in basic biology course to increase critical thinking

Abstract: Abstract. This research purposed to investigate the effect of integrated science model and its implementation in learning by Unity of Science in Basic Biology courses to improve students' critical thinking. This method research is a quasiexperimental with experimental design posttest only control group design. The population was all students of the first semester Biology, 2015/2016 academic year with consists of two classes. Samples were taken with a simple random sampling technique. The data was collected usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
1
Order By: Relevance
“…DRR is important to develop in order to understand events, experiences and objects on an individual level and is a social construct based on various experiences of one's life especially on religious experience. Preliminary research conducted on 20 students of Biology Education Department at UIN Walisongo, showed that student's PRB was influenced by previous education and student residence (Khasanah N. et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRR is important to develop in order to understand events, experiences and objects on an individual level and is a social construct based on various experiences of one's life especially on religious experience. Preliminary research conducted on 20 students of Biology Education Department at UIN Walisongo, showed that student's PRB was influenced by previous education and student residence (Khasanah N. et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Social construction based on various experiences of one's life especially DRR less attention. Ultimately meaningful learning is also poorly implemented in the lives of everyday students (Candra, 2012;Khasanah, N et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Learning often runs independently and is not integrated with religious values, because it is often assumed that religion is only limited to religious practices. The non-contextual teaching and learning process will hinder the development of students' ability to think holistically and make it difficult for them to relate the concepts they learn in the classroom to their daily life as a Muslim (Khasanah et al, 2017;Sunhaji, 2018). As a result, students are not given the opportunity to experience learning in real-world contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the times encourages transformation in education where everyone needs to have skills, and every learning process needs to develop 21st-century skills [1], [2]. In this era, critical thinking (CT) skills are the primary skills that need to be enhanced [3], [4].…”
Section: Introductionmentioning
confidence: 99%